Infrastructures of power: water governance on the Guatemala-México border - Mejía González, Ludivina (2026)
The aim of this contribution is to reflect on and analyze how the materiality of hegemonic infrastructures, such as hydroelectric projects, sustains a logic of fragmented governance carried out by a multiplicity of actors, including states, transnational corporations, and private companies. Along the Guatemala–Mexico border, the construction of hydroelectric projects continues to be a priority for national states and is driven by private companies seeking spaces for capital reproduction, with the support of international organizations. In particular, Northern Guatemala has become a niche for capital development, whose dynamics can be observed through coalitions reproduced across different scales. This text forms part of a broader research project that, methodologically, was developed through a multi-sited ethnography aimed at following the flows of the transboundary Santo Domingo River, shared by Mexico and Guatemala. Although the ethnography did not focus directly on infrastructures, the empirical findings allow them to be analyzed as central devices of water governance, insofar as hydraulic works and associated projects materialize political decisions, reconfigure water uses, and produce territorial conflicts.